Tropheryma whipplei detection by metagenomic next-generation sequencing in bronchoalveolar lavage fluid: A cross-sectional study - Lin, Minmin; Wang, Kongqiu; Qiu, Lidi; Liang, Yingjian; Tu, Changli; Chen, Meizhu; Wang, Zhenguo; Wu, Jian; Huang, Yiying; Tan, Cuiyan; Chen, Qijiu; Zheng, Xiaobin; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Tropheryma whipplei is the bacterium associated with Whipple’s disease (WD), a chronic systemic infectious disease primarily involving the gastrointestinal tract. T. whipplei can also be detected in different body site of healthy individuals, including saliva and feces. Few studies have explored the significance of the detection of T. whipplei in bronchoalveolar lavage fluid (BALF). Herein, we retrospectively reviewed 1725 BALF samples which detected for metagenomic next-generation sequencing (mNGS) from March 2019 to April 2022 in Zhuhai, China. Seventy BALs (70/1725, 4.0%) from 70 patients were positive for T. whipplei. Forty-four patients were male with an average age of 50 years. The main symptoms included cough (23/70), expectoration (13/70), weight loss (9/70), and/or dyspnea (8/70), but gastrointestinal symptoms were rare. Chronic liver diseases were the most common comorbidity (n=15, 21.4%), followed by diabetes mellitus (n=13, 18.6%). Only nine patients (12.9%) were immunocompromised. Twenty-four patients (34.3%) were finally diagnosed with reactivation tuberculosis and 15 patients (21.4%) were diagnosed with lung tumors, including 13 primary lung adenocarcinoma and two lung metastases. Fifteen patients (21.4%) had pneumonia. Among the 20 samples, T. whipplei was the sole agent, and Mycobacterium tuberculosis complex was the most common detected other pathogens. Among the non-tuberculosis patients, 31 (31/46, 67.4%) had ground glass nodules or solid nodules on chest CT. Our study indicates that T. whipplei should be considered as a potential contributing factor in some lung diseases. The mNGS technology improves the detection and attention of rare pathogens. In the future, the infection, colonization, and prognosis of T. whipplei in lung still need to be studied.